1998
DOI: 10.1029/98jd01483
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the organic nitrate yield from OH reaction with isoprene

Abstract: This paper describes the results of measurements of the branching ratio (k2b/(k2a + k2b)) for formation of organic nitrates via peroxy radical reaction with NO, following the reaction of the OH radical with isoprene (2‐methyl‐l,3‐butadiene). The experiments were conducted in a 5 m3 all‐Teflon photochemical reaction chamber, via the photolysis of isopropyl nitrite in the presence of isoprene and NO. The organic nitrate yield was determined from the measurement of the sum of all organic nitrate isomers, using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
186
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(200 citation statements)
references
References 24 publications
9
186
5
Order By: Relevance
“…Since the ratio of nitrate formation increases with the number of carbon atoms of the parent molecule, it was expected that the branching ratio of formation of the secondary nitrate from a-pinene would be larger than the corresponding ratio for 2-hexyl nitrate (19%) or cyclohexane (7-16%) [Lightfoot et al, 1991, and references therein]. However, as discussed in a recent work [Chen et al, 1998], the presence of the/3-hydroxy group next to the nitrate group should lower this branching ratio compared to the similar nitrate compound without the/3-hydroxy group.…”
Section: Reaction Of T•-pinene Withmentioning
confidence: 94%
“…Since the ratio of nitrate formation increases with the number of carbon atoms of the parent molecule, it was expected that the branching ratio of formation of the secondary nitrate from a-pinene would be larger than the corresponding ratio for 2-hexyl nitrate (19%) or cyclohexane (7-16%) [Lightfoot et al, 1991, and references therein]. However, as discussed in a recent work [Chen et al, 1998], the presence of the/3-hydroxy group next to the nitrate group should lower this branching ratio compared to the similar nitrate compound without the/3-hydroxy group.…”
Section: Reaction Of T•-pinene Withmentioning
confidence: 94%
“…The chamber is described in detail elsewhere (Chen et al, 1998). NO 3 and N 2 O 5 were produced in the chamber, via reactions 1 and 2, by injecting 400 ppbv of NO 2 and 145 ppbv of O 3 into dry zero air and allowing the mixture to react for ∼4 h.…”
Section: Methodsmentioning
confidence: 99%
“…Previous estimates for the isoprene nitrate yield, α, span a very large range. Chen et al (1998) reported an overall yield of 4.4%, Chuong and Stevens (2002), 15% using an indirect method, Sprengnether et al (2002), 12%, Patchen et al (2007), 7% at 130 hPa. Using experimental yields collected for compounds similar to isoprene, Giacopelli et al (2005) estimated the nitrate yield of the β and δ-hydroxy isoprene nitrates to be respectively 5.5% for the former and 15% for the latter, for an overall yield of 8.6%.…”
Section: Atmospheric Relevance 441 Fate Of Organic Nitrogenmentioning
confidence: 99%